2021
DOI: 10.1002/2211-5463.13209
|View full text |Cite
|
Sign up to set email alerts
|

Analogs of imine resveratrol alleviate oxidative stress‐induced neurotoxicity in PC12 cells via activation of Nrf2

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Moreover, plasma levels of superoxide dismutase, vitamin E, and nitric oxide were significantly reduced in a heterogeneous cohort of HSP patients suggesting inhibition of free radical scavenging activity [ 21 ]. Previous studies have indicated that antioxidants often achieve their neuroprotective activity by lowering ROS contents in cells; among others, resveratrol has shown great potential by directly scavenging overproduced ROS [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, plasma levels of superoxide dismutase, vitamin E, and nitric oxide were significantly reduced in a heterogeneous cohort of HSP patients suggesting inhibition of free radical scavenging activity [ 21 ]. Previous studies have indicated that antioxidants often achieve their neuroprotective activity by lowering ROS contents in cells; among others, resveratrol has shown great potential by directly scavenging overproduced ROS [ 22 ].…”
Section: Introductionmentioning
confidence: 99%